THE IMPACT OF THE COLLECTIVE INVESTMENT SCHEMES CONTROL ACT ON UNIT TRUSTS - MAZHAKATA, JOSHUA (My University, 2011)
The Collective Investment Schemes Control Act (2002), (CISCA) was promulgated into law on 12 December 2002 and became effective on 3 March 2003. CISCA introduces a number of changes to bring the Collective Investment Schemes in line with international practice. It replaces the Unit Trusts Control Act (1981) and the Participation Bond Act (1981). Three of the changes introduced by CISCA were investigated in the current study. CISCA removes the requirement to retain 5% of the fund‟s value in liquid assets. It allows the funds to fully invest in warrants and index tracking instruments. Securities by one concern can now hold the maximum of 5% or 10% (depending on market capitalisation) or 120% of the share‟s free float weighting in the relevant index, with an upper limit of 35% for any one share. An ex post study was conducted to establish what changes CISCA would have had on returns, had the legislation been introduced ten years prior to March 2003. A passive portfolio management strategy with a holding period of five years was used in the study. The study showed that investment in the Top 40 Tracker Fund yielded inferior returns compared to those for a unit trust fund. There was no statistically significant difference in returns for a fund with 5% cash and 95% equity, and a fund that had invested 100% of its assets in equity. However, the 100% equity fund yielded a marginally higher return of 1.1%. The changes introduced by CISCA are commendable as they create favourable conditions for investing in the unit trust industry.
MBA thesis - WBS
Keywords: Unit trusts; Investments; Collective investment schemes